A review of the physical context of creativity: A three-dimensional framework for investigating the physical context of creativity - Blomberg Annika J.; Kallio Tomi J. (Wiley, 2022)
Many organizations are investing considerable resources in building and designing what are termed 'creative offices'. In this paper, we bring together two lines of academic enquiry that have attracted the interest of scholars from different disciplines: organizational creativity and the physical space of organizations. These lines of study use different concepts and lean on different ontologies; consequently, their relation is underexplored in the extant literature. To provide a better understanding of the ways in which physical space relates to creativity, we offer an integrative review based on a three-dimensional framework comprising (i) the elements of workspace, (ii) the social dynamics of space and (iii) the relation between space and creativity. This framework is used to review the physical context of creativity literature. Based on this framework and our review, we outline three directions for future studies on the physical context of creativity. These directions are based on a broader understanding of physical space that aligns better with the contemporary conception of creativity as a process.